Could autism spectrum disorders be a risk factor for COVID-19? (2020)
The coronavirus SARS-CoV-2 pandemia is infecting millions of people and some studies relate conditions that might increase the risk of developing a fatal course for the disease, such as diabetes, cardiovascular diseases and obesity. In COVID-19 physiopathology, one of the main inflammation mechanisms is the “cytokine storm”, causing a pro-inflammatory state, related to cardiac and pulmonary damage. There is also a less effective role of lymphocyte B and T in the humoral immunity due to the reduction of their proliferative response. The physiopathology of ASD (Autism Spectrum Disorder) involves several modifications at the genetic and at the immune level, such as the increase of inflammatory cytokines and abnormal immune response in several levels. We hypothesize that ASD could be a risk-factor as the other conditions are.